Effects of a Short-Term Resistance-Training Program on Heart Rate Variability in Children With Cystic Fibrosis—A Randomized Controlled Trial - Estévez-González, Agustín Jesús; Donadio, Márcio Vinícius Fagundes; Cobo-Vicente, Fernando; Fernández-Luna, Álvaro; Sanz-Santiago, Verónica; Villa Asensi, José Ramón; Iturriaga Ramirez, Tamara; Fernández-del-Valle, Maria; Diez-Vega, Ignacio; Larumbe-Zabala, Eneko; Pérez-Ruiz, Margarita (Frontiers in Physiology, 2021)
Background: Cystic fibrosis (CF) affects the autonomic nervous system and exercise in healthy children modulates the interaction between sympathetic and parasympathetic activity. This study aimed to evaluate the effects of a short-term resistance exercise program on heart rate variability (HRV) in children and adolescents with CF. Methods: A randomized controlled trial was carried out in children diagnosed with CF aged 6 to 18 years. Individuals were divided into two groups: control (CON) and resistance-training (EX). Individuals in the EX group completed an individualized guided resistance program (5-RM - 60-80%) for 8 weeks (3 sessions of 60 min/week). Upper and lower limbs exercises (seated bench press, seated lateral row and leg press) were used. HRV was measured using a Suunto watch with subjects in lying position. Results: Nineteen subjects (13 boys) were included (CON=11; and EX=8). Mean age was 12.2±3.3, FEV1 (forced expiratory volume in the first second) z-score was 1.72±1.54 and peak oxygen consumption (VO2peak) 42.7±7.4 mL.Kg-1.min-1. Exercise induced significant changes in the frequency-domain variables, including a decrease in LF power (p=0.001, d=0.98) and LF/HF ratio (p=0.020, d=0.92), and an increase in HF power (p=0.001, d=-0.97), compared to the CON group. No significant changes were found for time-domain variables, although increases with a moderate effect size were seen for SDNN (p=0.152, d=-0.41) and RMSSD (p=0.059, d=-0.49) compared to the CON group. Conclusion: A short-term resistance exercise-training program was able to modulate HRV in children and adolescents with CF presenting mild to moderate lung function impairment and good physical condition.